2017
DOI: 10.1016/j.jaap.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Organic compound-mineral interactions: Using flash pyrolysis to monitor the adsorption of fatty acids on calcite

Abstract: Fatty acids are near ubiquitous organic compounds in living organisms in the Earth's biosphere. Following death of an organism in the marine environment its fatty acids may survive descent to the sea bed where they can be juxtaposed with minerals. The aim of this study was to investigate the interaction of fatty acids with the common marine mineral calcite. Adsorption of tetradecanoic acid (C14) on calcite results in a sigmoidal or "s" isotherm. Flash pyrolysis experiments were conducted on samples of fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Pyrolysis of tetradecanoic acid shows distinct products (Fig. 3), including alkenes which are the products of alkyl chain scission and alkanes such as tridecane which is the decarboxylation product of tetradecanoic acid (Zafar et al 2017). Along with that the saturated and unsaturated low molecular weight fatty acids are also produced as a result of alkyl chain scission and showed that chain scission is preferred over decarboxylation for the free fatty acid.…”
Section: Accepted Manuscript 15mentioning
confidence: 98%
See 4 more Smart Citations
“…Pyrolysis of tetradecanoic acid shows distinct products (Fig. 3), including alkenes which are the products of alkyl chain scission and alkanes such as tridecane which is the decarboxylation product of tetradecanoic acid (Zafar et al 2017). Along with that the saturated and unsaturated low molecular weight fatty acids are also produced as a result of alkyl chain scission and showed that chain scission is preferred over decarboxylation for the free fatty acid.…”
Section: Accepted Manuscript 15mentioning
confidence: 98%
“…Previously, our work showed that the symmetric ketone, 14-heptacosanone, formed from calcium tetradecanoate, further degraded to produce a homologous series of ketones and hydrocarbons (Zafar et al 2017). Pyrolysis products of a ketone-kaolinite mixture are significantly different from the chromatograms of fatty acid adsorbed kaolinite (Figs.…”
mentioning
confidence: 88%
See 3 more Smart Citations